A Chisel Generator for Standardized 3-D Die-to-Die Interconnects - Harrison Liew; Farhana Sheikh; Jong-Ru Guo; Zuoguo Wu; Borivoje Nikolic (IEEE Journal on Exploratory Solid-State Computational Devices and Circuits)
A 3-D heterogeneous integration (3-D-HI) is poised to enable a new era of high-performance integrated circuits via a multitude of benefits, including a reduction in I/O power consumption and ability to tightly couple disparate technologies. However, a significant hurdle toward enabling a chiplet ecosystem is the standardization of 3-D die-to-die (D2D) interconnects that facilitate rapid integration. Technology-driven constraints highlighted in published works demonstrate that a unique approach to 3-D D2D interconnect design and implementation is required, while preserving the ability to customize the interconnect to accommodate future technology concerns and applications with minimal overhead. This article presents a framework to generate customized 3-D D2D interconnect physical layers (PHYs) that are simultaneously standard-compliant, physical-aware, and can be automatically integrated into all stacked chiplets. The generator framework leverages the Chisel hardware description language to allow designers to do the following: 1) compile a port list directly into a PHY; 2) automate design and physical design (PD); and 3) perform design space exploration of interconnect features (e.g., bump map pitch, clocking architecture, and others). The 3-D PHY generator framework and features detailed in this work can be used to produce a reference implementation for a standard like UCIe-3-D, representing a significant paradigm shift from current specification and design methodologies for 2.5-D D2D interconnect (e.g., UCIe) implementations. This work concludes with the results of a redundancy design space exploration tradeoff study, showing the benefits of a proposed spatial coding redundancy scheme in an example PHY using emulated 9- $μ $ m hybrid bonding for a 4 Tx/4 Rx module array with 4:1 coding redundancy ratio.